Hubungan Kadar Hemoglobin Dengan Kejadian Dismenorea Pada Mahasiswi Universitas Pasir Pengaraian 2018 - Afriliana, Nana Aldriana, (Jurnal Martenity and Neonatal, 2019)
Dysmenorrhea is painful during menstruation, usually with cramps and concentrated in the lower abdominal area. Complaints of menstrual pain can occur ranging from mild to severe. The incidence of dysmenorrhea in the world is very large, on average more than 50% of women in each country have ever felt dysmenorrhea. Dysmenorrhea is caused by many factors, one of which is a low hemoglobin level. Dysmenorrhea in young women can cause a decrease in productivity and accomplishments. The purpose of this study was to determine the relationship of hemoglobin levels with the incidence of dysmenorrhea in students at the Pasir Pengaraian University. Method of quantitative analytic research with cross sectional approach. The population and sample in this study were all female students of the Midwifery Program at the Pasir Pengaraian University of 40 respondents. Data were collected using a questionnaire method using a checklist sheet. Data analysis was performed univariately and bivariately using the chi-square test. Research Results from the results of statistical tests, obtained the majority of respondents in this study had levels of Hbâ‰¥12gr / dl of 29 people (72.5%) and the majority of respondents also experienced dysmenorrhea of 21 people (52.5%), p value = 0.001 meaning there is a significant relationship between hemoglobin levels and the incidence of dysmenorrhea in the students of Pasir Pengaraian University. The conclusion is that there is a relationship between hemoglobin levels and the incidence of dysmenorrhea in the students of Pasir Pengaraian University in 2018. Suggestions that students maintain nutritional intake to maintain hemoglobin in normal levels.